2023
DOI: 10.3390/ijms24043110
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Infections and Cancer: Exploring This Association And Its Implications for Cancer Patients

Abstract: Bacterial infections are common in the etiology of human diseases owing to the ubiquity of bacteria. Such infections promote the development of periodontal disease, bacterial pneumonia, typhoid, acute gastroenteritis, and diarrhea in susceptible hosts. These diseases may be resolved using antibiotics/antimicrobial therapy in some hosts. However, other hosts may be unable to eliminate the bacteria, allowing them to persist for long durations and significantly increasing the carrier's risk of developing cancer o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 127 publications
0
21
0
1
Order By: Relevance
“…Our body harbours an estimated three trillion bacterial members that orchestrate a comprehensive interplay of physiological processes and disease susceptibilities (12) (13). Particularly in colorectal malignancies, these microbial organisms exercise their actions mostly through indirect channels (including metabolites and the immune system) on distant or proximal tumor tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…Our body harbours an estimated three trillion bacterial members that orchestrate a comprehensive interplay of physiological processes and disease susceptibilities (12) (13). Particularly in colorectal malignancies, these microbial organisms exercise their actions mostly through indirect channels (including metabolites and the immune system) on distant or proximal tumor tissues (14).…”
Section: Discussionmentioning
confidence: 99%
“…The interest in understanding the link between the microbiome and the development and progression of lung cancer has increased in recent years. It is known that the microbiome plays an important role in human health and disease by modulating a host's innate and adaptive immune system, immune responses, and metabolism, and by protecting from invading pathogens [235][236][237]. The tumor microenvironment (TME) influences cancer progression and therapy responses [238] and many recent studies have demonstrated associations between the TME and microbiota composition and responses to immune checkpoint inhibitors in cancer patients, including NSCLC patients, suggesting that modulation of the microbiota through diet, probiotics, and fecal microbiota transplantations (FMT) could improve treatment efficacy [238][239][240][241][242][243][244].…”
Section: Microbiomementioning
confidence: 99%
“…An elevated microbial presence within the oral cavity can generate substances that have the potential to exacerbate oral health issues, including periodontal diseases and tooth decay. [12] Additionally, the development and progression of oral cancer can be influenced by the interaction between the microbial population and their byproducts. This interplay is affected by multiple factors, including lifestyle habits, individual susceptibility, and genetic predisposition.…”
Section: Introductionmentioning
confidence: 99%
“…Continuity between oral infections and oral microbiology is evident. An elevated microbial presence within the oral cavity can generate substances that have the potential to exacerbate oral health issues, including periodontal diseases and tooth decay [12] . Additionally, the development and progression of oral cancer can be influenced by the interaction between the microbial population and their by‐products.…”
Section: Introductionmentioning
confidence: 99%